The Role of the Police in Uncovering Narcotics Offenses by Members of the Police (Study in Bengkulu Police Jurisdiction): Peran Kepolisian dalam Mengungkap Tindak Pidana Narkotika yang Dilakukan Anggota Kepolisian (Studi Di Wilayah Hukum Polda Bengkulu) - Pradityo, Randy; Kurniawan, Rizman (Akademi Kepolisian Republik Indonesia, 2021)
Narcotics crime has reached all circles, not only ordinary people who have become victims of narcotics abuse, even police officers who are law enforcers are also involved. The results of this study indicate the role of the police in the investigation and investigation of narcotics crimes carried out by members of the police at the Bengkulu Regional Police based on reports by the public, the results of routine urine tests and the results of investigations as well as the development of cases being investigated, but there is also a role for the Provos and Paminal Units to carry out the investigation. the preliminary examination (investigation) and the process of investigating the violation of the code of ethics and the Ditresnarkoba continue to the investigation process of criminal acts that have occurred in accordance with those stipulated in the Criminal Procedure Code and Government Regulation Number 3 of 2003 concerning the Technical Implementation of General Courts for the Police. The member concerned is immediately suspended from his post at the police service, from the time the investigation is carried out until a court ruling has permanent legal force.